#TITLE_ALTERNATIVE# - ADJIE KURNIYA - NIM. 18014041 , MAHARDHIKA
Based on Rencana Usaha Penyediaan Tenaga Listrik (RUPTL) of PT PLN 2017 – 2026, there is an increase in total peak load that connected to the two of main electrical system in Sumatra (Northern and Southern Electrical System) become 5946 MW at the end of 2016. Thus, the power system’s reliability is necessary because the failure in overcoming any disruptions that can occur anytime, will result in stalled of electrical energy supply to serve load demand across the island. One of the possible disturbances is the disturbance to small signal stability. The excitation control system of generator’s inability in facing small signal stability problems will cause the rotor’s oscillation at low frequencies continuously. Generally, the use of Automatic Voltage Regulator (AVR) raise the rotor’s synchronization torque without raising its damping torque value. Lack of damping torque will make the generator rotor oscillate. This non–muffled rotor oscillation will cause the generator loose from the system (out of step). Therefore, one solution that can be done is to make the arrangement (tuning) and activation of Power System Stabilizer (PSS) on the existing excitation control system. The control block diagram that owned by PSS can increase the damping torque and torque synchronization value of the generator in the same time so that the generator output response will be faster to reach steady state condition, shortly after the appearance of the disturbance. Eventually, the stability and reliability of Sumatra's electrical system from small signal stability disturbance will increase.